Managing acute pain in children presenting to the emergency department without opioids - Corrie E. Chumpitazi; Cindy Chang; Zaza Atanelov; Ann M. Dietrich; Samuel Hiu‐Fung Lam; Emily Rose; Tim Ruttan; Sam Shahid; Michael J. Stoner; Carmen Sulton; Mohsen Saidinejad; the ACEP Pediatric Emergency Medicine Committee (Journal of the American College of Emergency Physicians Open, 2022)
Abstract Pediatric pain is challenging to assess and manage. Frequently underestimated in children, untreated pain may have consequences including increased fear, anxiety, and psychological issues. With the current opioid crisis, emergency physicians must be knowledgeable in both pharmacologic and non‐pharmacologic approaches to address pain and anxiety in children that lead to enhanced patient cooperation and family satisfaction. This document focuses pain management and distress mitigation strategies for the brief diagnostic and therapeutic procedures commonly performed.